Pengaruh Atraksi, Aksesibilitas, Amenitas dan Kualitas Pelayanan Terhadap Minat Kunjungan Ulang Wisatawan di Pulau Kumala Kabupaten Kutai Kartanegara - Dita, Riri Febria; Zaini, Muhammad (Rifa'Institute, 2022)
The tourism industry in Indonesia continues to grow along with the development of technology, transportation, and information. So that companies or tourism business actors must pay attention to tourism marketing by promoting service products and service quality in these tourist destinations. Kumala Island is a leading tourist attraction in Kutai Kartanegara Regency. The purpose of this study was to determine the effect of attractions, accessibility, amenities, and quality of service on the interest in repeat visits to Kumala Island, Kutai Kartanegara Regency. This study uses primary data by distributing questionnaires. The population in this study are visitors who have visited Kumala Island, with a sample of 100 respondents using thetechnique Accidental Sampling. The data analysis of this research uses multiple linear analysis using SPSS version 25.The results of this study prove that the Attraction variable partially has a positive and significant effect on Tourist Revisit Interest. Then the accessibility variable partially has a positive and significant effect on Tourist Revisit Interests. The Amenity variable partially has a positive and significant effect on Tourist Revisit Interests. Furthermore, the service quality variable partially has no positive and insignificant effect on Tourist Revisit Interests. Furthermore, simultaneously attractions, accessibility, amenities and quality of service partially have a positive and significant effect on Tourist Revisit Interests. The conclusion of this study explains that partially between the variables of attraction, accessibility, amenity have a positive and significant influence on the interest of repeat tourists. While the quality of service does not have a positive and insignificant effect on the interest of repeat tourists, but simultaneously the variables of attraction, accessibility, amenity and service quality have a positive and significant influence on the interest of repeat tourists.